Implementation of Problem Based Learning (PBL) Learning Model to Improve Mathematical Critical Thinking Skills and Learning Motivation of Grade 5 Students at UPT SD Negeri Kutorejo 3 Tuban - Khotimah, Siti Nurul; Wulandari, Tabitha Sri Hartati (Indonesian Journal of Education and Mathematical Science, 2025)
This study aims to improve the mathematical critical thinking skills and learning motivation of 5th grade students of UPT SDN Kutorejo 3 Tuban through the application of the Problem Based Learning (PBL) learning model with material comparing and sorting fractions. This study uses a Classroom Action Research (CAR) approach consisting of two cycles. The subject of the study was grade 5 students with a total of 29 students. The instruments used in this study include tests to assess mathematical critical thinking skills, learning motivation questionnaires, and observation sheets of the learning process. The results showed a significant increase in students' mathematical critical thinking skills and learning motivation after the application of the PBL model. In the first cycle, 69% of students achieved completeness in the critical thinking test, while 31% of students did not complete it. Based on the results of the questionnaire, 40% of students showed low motivation to learn. In the second cycle, the percentage of completeness increased to 75.8%, with 22 students achieving completeness. In addition, students' motivation to learn also increased, with 87.84% of students showing higher motivation compared to the first cycle. Thus, it can be concluded that the application of the PBL model is able to encourage the improvement of mathematical critical thinking skills and learning motivation of 5th grade students at UPT SDN Kutorejo 3 Tuban.